Investigating the effect of zinc supplementation on probability of relapse and mental health in patients with opioid use disorder undergoing methadone maintenance treatment - Zahra Amini; Ebrahim HeidariFarsani (BMC, 2023)
Abstract Background Considering different factors, such as high withdrawal rates in methadone maintenance treatment (MMT) programs alongside mental health (MH) problems appearing in patients with opioid use disorder and the lack of prior research on the effect of zinc supplementation in this respect, the present study aimed to investigate the effect of zinc supplementation on the probability of relapse (PoR) and MH problems in patients with opioid use disorder undergoing MMT. Methods For this purpose, a randomized controlled trial with a clinical basis was fulfilled on a total of 68 patients with opioid use disorder receiving MMT, allocated to two groups, viz. intervention, and control (each one consisting of 34 individuals). Then, the participants in the intervention group were given zinc supplements combined with methadone for three months, and the controls only took methadone, according to the treatment plan. The data were collected using the Relapse Prediction Scale (RPS) and the Depression, Anxiety, and Stress Scale 21 (DASS-21) before, one month after, and at the end of the intervention program. Findings Compared to the control group, the likelihood of drug use (p = 0.01), drug craving (p = 0.002), and the RPS total score (p = 0.002) in the intervention group was significantly lower. Moreover, the results revealed a significant decreasing trend in depression (p = 0.01), anxiety (p < 0.001), stress (p = 0.001), and the DASS-21 total score (p = 0.001) in the intervention. Compared to the control group, the DASS-21 total score (p < 0.001) in the intervention group was significantly lower. Conclusion Accordingly, it was concluded that zinc supplementation could reduce the PoR and improve MH problems in patients with opioid use disorder experiencing MMT. However, further research is recommended to fill the gaps. Trial registration The research protocol has also been listed on the Iranian Registry of Clinical Trials (IRCT) with code no. IRCT2020050904736N1.